Cost Effective Analysis of Single and Combine Antipsychotics Therapy for Schizophrenia Patient West Java Mental Hospital - Arum Febriyanti, Nida
Antipsychotics are the main pharmacological therapy for schizophrenia. The use of antipsychotic in schizophrenia treatment is often followed by cost related issues. Cost problems occur because schizophrenia is a severe psychopathology which usually need lifetime pharmacological therapy. thus requiring considerable cost. From government's perspective as national insurance provider, treating schizophrenia takes large portion of health care yearly budget. To solve this problem, further analysis is necessary to determine the type of therapy that is most cost-effective. The aim of the study was to compare the effectiveness of schizophrenia treatment using monotherapy combined with several antipsychotics. In addition, hospital charges were also compared to determine which antipsychotics were more cost effective. The pharmacoeconomy research was conducted using cost-effectiveness method which was done retrospectively on patients in West Java mental hospital from June-December 2014. This was followed by calculating the probability and mathematical modeling with a decision tree to get the cost of each group and calculate the Incremental cost effective ratio (ICER). Based on the results of the study, the type of antipsychotic therapy used in the acute phase and the stable phase in the Mental Hospital is monotherapy second generation antipsychotic (SGA), monotherapy first generation antipsychotic (FGA), SGA combination therapy, combination therapy, and combination therapy FGA FGA and SGAIt was found that second generation antipsychotic (SGA) monotherapy was the most effective compared to other antipsychotic because SGA symptom-free days was longer in both acute and stable phases. In terms of cost, SGA monotherapy is the most inexpensive in both acute and stable phases. Based on ICER analysis, in acute phase of therapy, monotherapy SGA was more cost effective than combination therapy of SGA, the combination of FGA and the combination FGA and SGA, with ICER value of Rp -350.478,- residing in second quadrant. In stable phase, the use of monotherapy SGA was more cost effective than combination therapy of SGA and FGA or SGA combination therapy, with an ICER value amounting to -Rp 230.589 occupying second quadrant. The result of this study demonstrated thet the most effective type of therapy based on the analysis of ICER in the acute phase and the stable phase of schizophrenia is SGA monotherapy.